2020
DOI: 10.1016/j.cognition.2020.104335
|View full text |Cite
|
Sign up to set email alerts
|

Definitely saw it coming? The dual nature of the pre-nominal prediction effect

Abstract: In well-known demonstrations of lexical prediction during language comprehension, pre-nominal articles that mismatch a likely upcoming noun's gender elicit different neural activity than matching articles. However, theories differ on what this pre-nominal prediction effect means and on what is being predicted. Does it reflect mismatch with a predicted article, or 'merely' revision of the noun prediction? We contrasted the 'article prediction mismatch' hypothesis and the 'noun prediction revision' hypothesis in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 87 publications
(171 reference statements)
14
60
0
Order By: Relevance
“…Instead of the materials used in the original study (VB05), we used a suitable set of stimuli readily available from a previous study (Fleur et al, 2020). This set of materials was created following a similar procedure as that of the original, was larger than that of the original, and had already been normed for cloze probability.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Instead of the materials used in the original study (VB05), we used a suitable set of stimuli readily available from a previous study (Fleur et al, 2020). This set of materials was created following a similar procedure as that of the original, was larger than that of the original, and had already been normed for cloze probability.…”
Section: Methodsmentioning
confidence: 99%
“…In a subsequent experiment with written Spanish sentences but without accompanying drawings, Wicha et al (2004) found that gender-mismatching articles elicited a different pattern, namely a positive ERP effect (P600) compared to matching articles. In more recent studies on comprehension of written sentences, gender-mismatch on prenominal articles was associated with N400-like effects, i.e., an enhanced negativity in the typical N400 time window (Dutch: Fleur, Flecken, Rommers, & Nieuwland, 2020;Otten & Van Berkum, 2009;Spanish: Foucart, Martin, Moreno, & Costa, 2014;Martin, Branzi, & Bar, 2018;Molinaro, Gianelle, Caffarra & Martin, 2017), although sometimes with a time course or scalp distribution unlike the typical N400 effects elicited by nouns.…”
Section: 1mentioning
confidence: 96%
See 3 more Smart Citations